Strategi Pengembangan Ekosistem Perbankan Digital Komunitas di Wilayah Perbatasan Indonesia- República Democrática de Timor-Leste (RDTL) - Hany Bengu; Moshe Markhasi Rupilu; Femberianus Sunario Tanggur (SENTRI: Jurnal Riset Ilmiah, 2025)
Digital transformation in the financial sector presents significant opportunities to expand financial inclusion in border regions, such as Belu Regency, Indonesia, which shares a direct border with the Democratic Republic of Timor-Leste (RDTL). However, developing a community-based digital banking ecosystem in this area faces numerous challenges. This study aims to identify barriers and formulate contextual strategies for building inclusive digital financial services. Using a descriptive qualitative approach and case study method, data were collected through in-depth interviews, field observations, and documentation involving local communities, financial service providers, and local government officials. Thematic analysis was employed, supported by SWOT analysis. The findings reveal key obstacles, including limited network infrastructure, low levels of digital literacy and trust, the dominance of cash transactions and traditional financial systems such as arisan, as well as socio-economic and cross-border regulatory challenges. The study recommends inclusive, locally grounded digital transformation strategies, including a hybrid approach combining conventional and digital services, expanding infrastructure and digital security education, and digitizing community financial systems like arisan and cooperatives. This approach is expected to promote sustainable and context-sensitive financial inclusion in border areas.